2014
DOI: 10.1249/01.mss.0000494467.53181.62
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Cerebral Autoregulation Is Acutely Impaired During Maximal Apnoea In Trained Divers

Abstract: Aims: To examine whether dynamic cerebral autoregulation is acutely impaired during maximal voluntary apnoea in trained divers.Methods: Mean arterial pressure (MAP), cerebral blood flow-velocity (CBFV) and end-tidal partial pressures of O 2 and CO 2 (PETO 2 and PETCO 2 ) were measured in eleven trained, male apnoea divers (2862 yr; 18262 cm, 7667 kg) during maximal ''dry'' breath holding. Dynamic cerebral autoregulation was assessed by determining the strength of phase synchronisation between MAP and CBFV duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
5
1
Order By: Relevance
“…Compared to other studies our measured MAP increase was higher (31 mmHg at Cross et al [12], 32 mmHg at Heusser et al [22], and 17 mmHg at Perini et al [36]). The mean apnea time lasted 247 ± 76 s, which is longer than those reported by the mentioned studies (199 ± 11 s [12] and 210 ± 70 s [36]) for trained divers and in the same range as the 234 ± 66 s published by Heusser et al [22] for elite divers. Thus, the divers in this study may be classified as well-trained in the field of static apnea and the detected apnea dependent compensatory mechanisms can be classified as relatively distinct.…”
Section: Blood Pressure Apnea Duration and Cocontrasting
confidence: 87%
“…Compared to other studies our measured MAP increase was higher (31 mmHg at Cross et al [12], 32 mmHg at Heusser et al [22], and 17 mmHg at Perini et al [36]). The mean apnea time lasted 247 ± 76 s, which is longer than those reported by the mentioned studies (199 ± 11 s [12] and 210 ± 70 s [36]) for trained divers and in the same range as the 234 ± 66 s published by Heusser et al [22] for elite divers. Thus, the divers in this study may be classified as well-trained in the field of static apnea and the detected apnea dependent compensatory mechanisms can be classified as relatively distinct.…”
Section: Blood Pressure Apnea Duration and Cocontrasting
confidence: 87%
“…Here, despite further increases in MAP with apnoea, the elevations in CBF are attenuated (probably via increases in ICP). In contrast, when reported using a transfer function analysis (Cross, Kavanagh, Breskovic, Johnson, & Dujic, ), cerebral autoregulation appears impaired. Nonetheless, a caveat to both studies is the negation of ICP in determining the CPP.…”
Section: Cerebrovascular Regulationmentioning
confidence: 89%
“…Indeed, it has been recently shown that the diameter of the MCA is not static. 5,7,11,39 Cross et al 40 interpreted increased phase synchronization during apnea to indicate impaired cerebral autoregulation, but various metrics that ostensibly quantify the efficacy of cerebral autoregulation have been shown to yield disparate results. 32 However, that CBF did not increase further than during clamp despite a much greater increase in MAP is evidence of cerebral autoregulatory efficacy without the confounding influence of more quantitatively complex metrics of autoregulation and the potentially invalid assumptions of transcranial Doppler ultrasound.…”
Section: Cerebral Autoregulation During Apneamentioning
confidence: 99%